Let's apply the distributive property to each part of the expression:
2(a+5) = 2a + 10
4(2a+3) = 8a + 12
Now, we can combine like terms:
2a + 10 + 8a + 12 - 10
Simplifying further:
10a + 12 + 2
Final expression:
10a + 14
Apply the Distributive Property and Combine like Terms to generate an expression equivalent to 2(a+5)+4(2a+3)−10
3 answers
You sure?
Apologies for the mistake. Let's redo the calculations:
2(a+5) = 2a + 10
4(2a+3) = 8a + 12
Now, we combine like terms:
2a + 10 + 8a + 12 - 10
Simplifying further:
10a + 22 - 10
Final expression:
10a + 12
2(a+5) = 2a + 10
4(2a+3) = 8a + 12
Now, we combine like terms:
2a + 10 + 8a + 12 - 10
Simplifying further:
10a + 22 - 10
Final expression:
10a + 12